Desenvolvimento e composição centesimal de formulações de biscoitos com farinha de casca de cacau (theobroma cacao) adicionados de mel de abelhas-sem-ferrão - Reis, Jocastra Alexandra de Souza (Brasil, 2024)
The objective of this study was to develop two formulations of biscuits using cocoa hull flour (FCC), stingless bee honey (ASF) and analyze its proximate composition. The proximate composition of the FCC and the two biscuit formulations (F1 – with ASF honey and F2 – without ASF honey) was determined in triplicate, according to the official analytical standards for food analysis. The FCC showed 6.2 ± 0.2% humidity; 7.85 ± 0.09% ash; 9.10 ± 0.27% protein; 1.19 ± 0.06% lipids and 75.05% total carbohydrates. F1 had 6.7 ± 0.2% humidity; 2.00 ± 0.02% ash; 9.43 ± 0.75% protein; 33.62 ± 0.55% lipids and 47.99% total carbohydrates. F2, on the other hand, had 5.7 ± 0.1% humidity; 1.75 ± 0.07 ash; 10.0 ± 0.39% protein; 37.43 ± 2.09% lipids and 44.81% carbohydrates. Only the moisture content showed a significantly different value between F1 and F2 (p < 0.05). The predominant nutrients in the flour were carbohydrates and proteins; In the biscuits, it was the carbohydrates and lipids. The products developed are an option to reduce the production of solid waste generated in the food industry.